Experimental studies on thread-fixed one-side bolted endplate connection with internal strengthening structure. (1st November 2021) - Liu, Mei; Zhang, Boxun; Liu, Quanwei; Liu, Yuanjian; Tang, Liru; Zhang, Wenchao; Liu, Fangzhou; Wang, Peijun
Highlights: Two novel internal strengthening structures to TFOSBEC were proposed and tested. Four typical failure modes occurred and discussions of test results were presented. The performance of strengthened TFOSBEC was improved significantly. Double H-shaped stiffener could better improve the connection yielding bending moment. Calculation methods were proposed to predict the yielding bending moment of TFOSBEC. Abstract: The thread-fixed one-sided bolt has excellent potential application in engineering practice thanks to its low cost and easy installation. However, there must be a sufficient length of threads on the hollow square column wall to prevent the threads from premature failure. This paper proposed two novel internal strengthening structures to strengthen the thread-fixed one-sided bolted beam to hollow square column endplate connection and experimentally studied the behavior of this type of connection. A total of six specimens subjected to static bending moment were tested. The experimental results were analyzed in this paper to evaluate the structural performance of the strengthened connection and the efficiency of different strengthening structures. It was indicated that the double H-shaped stiffener could better improve the yielding bending moment of the connection, compare to polygonal steel tube stiffener. And the bolt hole threads failure and the column wall yielding failure could be avoided at the same time by utilizing strengthening structures moderately, which proved that this type of connection could meet the design criteria of "strong column - weak beam". Moreover, based on the test results and theoretical analysis, the calculation methods for corresponding failure modes were proposed to predict the yielding bending moment capacity of the strengthened connection. And the calculated results were in good agreement with the test results.